Evaluation of safety and efficacy of a new device for muscle toning and body shaping. (29th October 2021) - Leone, Alessandro; Piccolo, Domenico; Conforti, Claudio; Pieri, Laura; Fusco, Irene
Abstract: Background: The spread of non‐invasive procedures for fat deposits removal has increased rapidly in recent years. In the field of esthetic medicine, high‐intensity focused electromagnetic field (HIFEM) technology has recently been introduced, as a tool for toning and strengthening muscles, which goes far beyond normal physical exercise. Objective: The purpose of this study is to evaluate the efficacy and safety of a new device for body remodeling. Methods: A set of 15 patients (7 males and 8 females, BMI 24.05 ± 2.01 kg m −2, age 32–57) participated in this study. Patients were enrolled at Dermatos center, Montesilvano, Abruzzo, Italy. The technology used is FMS (Flat Magnetic Stimulation): 6–8 treatment sessions were performed. The sessions must be repeated twice a week, with a minimum of 2 days between each session. Treatment duration varies from 20 to 45 min, depending on patients. Results: During 1‐month follow‐up after the last treatment evaluations, the results showed tonification, the strengthening of muscles, and the reduction of localized adiposity. There is a significant reduction in waist circumference (80.7 ± 4.3 cm vs 77.3 ± 5.6 cm, p  < 0.001). All patients showed relatively high satisfaction immediately after the last treatment. Conclusions: Our data show that intense muscle activity is generated by FMS treatments, suggesting that this technology could be used as a convenient and effective muscle toning tool.